An ultrasound study of foetal head-perineum distance in term pregnant women to estimate successful vaginal delivery - Vijayakrishnan, Mala; Nathan, Navina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The aim of the study is to find the role of foetal head-perineum distance in term primiparous pregnant women being induced, in estimating successful vaginal delivery using transperineal ultrasound. And further to compare fetal head-perineum distance with cervical length and Bishop score. Cervical length and Bishop score were already established as good predictors of vaginal delivery. Methods: An ultrasound machine with transabdominal and transvaginal probe was used in the study. In this study spanning from December 2023 to October 2024; 63 primiparous term pregnant women were recruited from Vijaya hospital, Chennai after getting approval from the Institutional Ethical Committee. 63 primiparous patients who underwent induction of labour for various reasons were selected for the study and examined. Patients undergoing elective induction of labour at term gestation were assessed for the fetal head-perineum distance (FHPD) by transperineal ultrasound and cervical length by transvaginal ultrasonography. Bishop score was assessed digitally. After induction of labour, patient undergoing vaginal delivery and caesarean sections were noted down. Results: Forty-two patients delivered vaginally. Twenty-one patients delivered by LSCS. Fetal head-perineum distance cut-off in my study was 5.5 cm. Cervical length cut-off was 3cm. Patients having favorable bishop score of 5 and above delivered vaginally. Conclusions: Trans perineal fetal-head perineum distance measured by ultrasound can be used as an important tool to predict vaginal delivery before induction of labour.